Novel Positional Candidate Gene for Gait Speed Change in Older Adults: The Long Life Family Study. (17th December 2021) - Wojczynski, Mary; Cvejkus, Ryan; Thyagarajan, Bharat; Christensen, Kaare; Schupf, Nicole; Daw, E Warwick; Zmuda, Joseph; Santanasto, Adam
Abstract: Gait speed is a heritable, robust predictor of longevity in older adults. Using genome-wide linkage analysis in 2379 individuals from 509 families (64±12 years; 45% men), we identified a locus on chromosome 16p linked to gait speed change over 7±1 years (logarithm of the odds score [LOD]=4.2). Gait speed change was calculated using a two-stage growth curve mixed-model. DNA sequencing was completed to identify single nucleotide variants (SNVs) in the linkage region. Association analyses between the 24039 SNVs in the ~1.6mBP region (3.7-5.3mBP) and gait speed change were performed adjusting for age, age2, sex, height, field center, familial relatedness and population substructure. Eleven families (188 individuals) accounted for most of the linkage signal (LOD=6.06). Associations between SNVs flanking the Mesothelin (MSLN) gene and gait speed change were identified (lead SNV rs56850119: β = -0.5±0.1, p = 6.4*10-7). Thus, MSLN is a potential positional candidate gene for mobility decline with aging.